2021
DOI: 10.14202/vetworld.2021.1109-1115
|View full text |Cite
|
Sign up to set email alerts
|

The effect of different types of in ovo selenium injection on the immunity, villi surface area, and growth performance of local chickens

Abstract: Background and Aim: The presence of free radicals may lower chicken's performance. Thus, the antioxidant defense is needed and can be made through a nutritional approach such as selenium supplementation before hatches. This study aimed to investigate the type of selenium that, as an in ovo feeding (IOF) material, can provide the most enhancement of immunity, villi surface area, and early growth performance of local chickens. Materials and Methods: This study, with a completely randomized design, used 480 fert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 28 publications
(30 reference statements)
1
10
0
Order By: Relevance
“…These results agree with Rajkumar et al (2015), who explained that IOF of vitamin E and glutamine helps in protecting the intestinal mucosa enterocytes, which consequently are involved in increasing cell proliferation and villus growth (Murakami et al 2007). Furthermore, IOF of organic or inorganic Se on day 18 of incubation increased villus surface area and villus length and width in the duodenum and ileum (Krisnan et al 2021).…”
Section: Impact Of In Ovo Feeding Of Nutraceuticals On Modulating Gut...supporting
confidence: 90%
See 4 more Smart Citations
“…These results agree with Rajkumar et al (2015), who explained that IOF of vitamin E and glutamine helps in protecting the intestinal mucosa enterocytes, which consequently are involved in increasing cell proliferation and villus growth (Murakami et al 2007). Furthermore, IOF of organic or inorganic Se on day 18 of incubation increased villus surface area and villus length and width in the duodenum and ileum (Krisnan et al 2021).…”
Section: Impact Of In Ovo Feeding Of Nutraceuticals On Modulating Gut...supporting
confidence: 90%
“…The IOF of trace elements has gained extra attention due to their multiple physiological roles, such as activating several vital enzymes, promoting immunity, and alleviating the oxidative stress. Krisnan et al (2021) indicated that IOF of 0.15 ppm of organic or inorganic Se on day 18 of incubation improved the antibody titre against Newcastle disease virus and lymphocyte and heterophil percentages. These results are consistent with Ibrahim et al (2020), who illustrated that IOF of 10 ppb of nano-Se on day 18 of incubation increased serum concentrations of IgM, IgG, and total immunoglobulins and antibody titre against Newcastle disease virus.…”
Section: Impact Of In Ovo Feeding Of Nutraceuticals On Immune Responsementioning
confidence: 95%
See 3 more Smart Citations